Peran Pendamping Program Keluarga Harapan Terhadap Pemberdayaan Masyarakat Lassang Barat Takalar - Nur Afni; Syamsuddin AB (Jurnal Berita Sosial, 2022)
The Role of the Family Hope Program Facilitator on Community Empowerment and the Facilitator's Obstacles in the Role of the Hopeful Family Program for the Empowerment of the Poor. This research is a qualitative research with Sociological approach method, while the location of this research is in Lassang Barat Village, Polongbangkeng Utara District, Takalar Regency. The sources of data in this study are primary data sources and secondary data sources. Data collection methods are by observation, interviews, and documentation. Research instruments using cameras, notebooks, recording devices, and interview guidelines. After all the data is collected, the researcher then analyzes the data with data reduction. Presentation of data (data display), and drawing conclusions (drawing conclusion). The results of this study indicate that the roles of PKH facilitators in Lassang Barat Village are: 1). The role of the facilitator during the initial meeting and data validation, 2). The role of the facilitator during verification of eligibility, 3). The role of the facilitator during data updating, 4) The role of the facilitator when facilitating the process complaints and, 5). The role of the companion during routine assistance. The obstacles for companions in the role of the Family Hope Program in West Lassang Village are divided into 3 obstacles, namely obstacles when providing understanding to the people who receive PKH assistance. The two obstacles faced by the facilitators were differences of opinion with the local government. The three obstacles faced by the facilitator are the lack of rest time for the companion.